Case of catheter ablation of atrial fibrillation in a very young patient without structural heart disease. Issue 3 (18th March 2022) - Sawasaki, Kohei; Hosoya, Natsuko; Muto, Masahiro
Abstract: The patient was an 18‐year‐old man who suffered frequent supraventricular premature complexes (SVPCs) and atrial fibrillation. Catheter ablation was performed, and the left pulmonary vein had been isolated, although firing from within the left inferior pulmonary vein remained. After that, the patient did not exhibit SVPCs and atrial fibrillation. Abstract : Regardless of patient age, the pulmonary vein is highly likely to be the source of arrhythmogenic activity causing atrial fibrillation. Currently, it is possible to radically cure atrial fibrillation with ablation via pulmonary vein isolation.